Investigating the implementation of a Trial of Labour After Caesarean (TOLAC) delivery bundle with respect to decreasing caesarean delivery rates: a multisite quality improvement initiative - Eliane M Shore; Elizabeth Miazga; Cheyanne Reed; Alisha Olsthoorn; Isabella Fan; Eliya Zhao; Jodi Shapiro; Amanda Cipolla; Modupe Tunde-Byass (BMJ Open)
Objectives To study the effect of implementing a Trial of Labour After Caesarean (TOLAC) delivery bundle with respect to decreasing caesarean delivery rates across five hospitals.Design Prospective quality improvement study.Setting Five Canadian hospital sites participated, two academic centres and three community hospitals, with annual delivery rates ranging from 2500 to 7500 per site.Participants All obstetrical patients with a singleton gestation in cephalic presentation and only one previous caesarean delivery were included.Interventions A TOLAC bundle was introduced at each hospital site, consisting of three main interventions: (1) education for healthcare providers, (2) a TOLAC discussion sheet and (3) patient educational tools.Primary and secondary outcome measures The primary outcome was the caesarean delivery rate in eligible patients. Secondary outcomes included rates of trial of labour after caesarean delivery, vaginal birth after caesarean delivery and induction of labour. Balance measures included rates of uterine rupture and neonatal intensive care unit admission. Process measures included attendance at educational rounds, elements of the interventions identified in chart review and view counts for educational videos.Results The baseline caesarean delivery rate was 77% (1730 out of 2244 eligible patients). Following the introduction of the bundle, the caesarean delivery rate decreased to 71% (1497 out of 2097 eligible patients; 6% decrease, p<0.001). A significant increase in induction rate was noted from 5% preintervention to 9% postintervention (p<0.001). There was no increase in the uterine rupture or neonatal intensive care admission rates.Conclusion This TOLAC bundle can decrease caesarean delivery rates without negatively impacting uterine rupture or neonatal intensive care admission rates. The interventions can be easily adapted for use in different hospitals and practice environments.